Towards a Legislative Reform in Denmark? - Motzfeldt, Hanne Marie (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2019)
The digital transformation of the public sector in Denmark has been going on steadily for almost twenty years and has changed the Danish public authorities’ working processes, organization and interaction with citizens. In this article, it is briefly described how national administrative law developed as a response to comparable changes in the Danish public sector in the 1950s to the 1980s. It is assumed that this past development primarily was driven by the need to protect fundamental values embedded in the Danish legal culture. Further, it is examined whether there is any trace of a similar development related to the present digital transformation. Finally, as such a development in Danish case law can be observed, it is assessed whether a legislative reform within administrative law is likely to be initiated and adopted within the next decade.